Migration in the People's Republic of China - Ming Lu; Yiran Xia (Asian Development Bank Institute (ADBI), 2016)
This report summarizes the characteristics of migration in the People's Republic of China (PRC) after its reforms and opening up. Rapid urbanization in the PRC has resulted from recent decades of intense rural-urban migration. The scale of migration increased rapidly and long-term migration is the main characteristic. The population characteristics of migration are determined not only by a personal decision, but also a joint decision within households to send members with comparative advantages in manufacturing and services, usually male and young, to work in cities. Coastal regions where manufacturing and services are better developed, especially big cities, are the major destinations. The aspiration for higher-income and better job opportunities is the major force that drives migration, while public services and urban amenities also partly account for population flows. However, in the PRC, there are still major institutional barriers - especially the hukou system and related segmentation in the urban labor market, social security, and public services access - that hinder rural-urban and interregional migration. Facing the challenges of fast urbanization and growing urban diseases, local governments still rely on the current system to control the population flow into large cities. Controlling population growth by discriminative policies will lead to more social problems. Policy makers should reconsider the way to achieve efficient and harmonious urbanization by shifting to more pro-market policies and reducing the migration costs embedded in institutional constraints.
Keywords: J61; P25; R23; 330; migration; rural-urban migration; PRC; urbanization; hukou system; People's Republic of China; rapid urbanization